Alveolar soft-part sarcoma of the orbit - Rose Anna; Kabiru Joy; Rose Geoffrey (Wolters Kluwer Medknow Publications, 2011)
Alveolar soft-part sarcoma (ASPS) is a rare soft tissue tumour of uncertain cellular origin. It accounts for only 1% of all sarcomas, which themselves represent only a small proportion of human tumours. ASPS can arise in any soft tissue of the body, but there is an unexplained predilection for the right side. The most common site for paediatric ASPS is in the head and neck region, although involvement of the orbit is rare, with fewer than 30 reported cases. A case of a 5-year-old Kenyan boy with left-sided orbital ASPS is reported and the difficulties of diagnosing rare tumours are discussed.